Autoimmune diseases after allogeneic stem cell transplantation: a clinician's guide and future outlook. (3rd June 2022) - Faraci, Maura; Dell'Orso, Gianluca; Giardino, Stefano; Pierri, Filomena
ABSTRACT: Introduction: Autoimmune disease (AD) may occur after allogeneic hematopoietic stem cell transplantation (HSCT). The autoimmune mechanism seems to be related to an imbalance of the immune regulation effect of T-regulatory lymphocytes on autoreactive T-lymphocytes. Areas covered: ADs include hematological ADs (HADs) and nonhematologic ADs (NHADs) involving organs such as thyroid, peripheral and central nervous system, skin, liver, connective tissue, gastrointestinal tract, and kidney. To identify the risk factors for ADs, to report their clinical characteristics, and to discuss new approaches represent the areas covered in this review. Expert opinion: Some risk factors for HAD and NHAD are common and include nonmalignant diseases, young age, cord blood as a stem cell source, conditioning regimens without total body irradiation, alemtuzumab, antithymocyte globulin, T-cell-depleted transplant, some viral infection, mixed chimerism, and chronic Graft versus Host Disease. In NHADs, the detection of autoantibodies is more frequent and the transfer of autoimmunity from the donor to the recipient represents the pathogenetic mechanism responsible for these complications. New therapeutic approaches such as bortezomib, daratumumab, sirolimus, eculizumab, and eltrombopag appear to be promising in terms of better efficacy and reduced toxicity compared to traditional therapies. New horizons based on personalized therapies will allow us to improve the prognosis of AD.